O alçamento das vogais posteriores em sílaba tônica: um estudo do português falado em Borba no Amazonas - Campos, Maria Sandra (2009)
This work has dealt with the phenomenon of the rising the tonic position back vowels in the speech of the inhabitants of the Municipal District of Borba in the State of Amazonas. This study has been theoretically supported by linguistic principles and reviewed under the sociolinguistic perspective. It is, thus, underpinned by previous phonetic and phonological studies and by qualitative and quantitative analysis of data (this in percentage terms). For the analyses, diastractic and diatopic factors, such as, age, gender and place, in addition to linguistic factors will be used as a thermometer, an on them shall weigh the responsibility for verifying if the phenomenon is already going through transformation. We have elected a corpus requiring the participation of twenty-four informants allocated in four groups. For each one of them, we chose three subgroups representing such factors as age and gender. Research results have shown that the rising is recurrent in the region under study. They have also shown that this is not an exclusive prerogative of the individuals of the rural zone, as we had envisioned. We have identified it in the speech of the citizen from Borba living in the urban zone, that is, he who lives in the seat of the municipality. We have outlined the profile of the man and the physical space of the region, as a way of understanding the factor as intermediators in the linguistic variations occurring in the Borba speech